The push-pull effects of the information technology boom and bust: insight from matched employer-employee data - Julie L. Hotchkiss; M. Melinda Pitts; John C. Robertson (Federal Reserve Bank of Atlanta, 2006)
This paper examines the inflow and outflow of workers to different industries in Georgia during the information technology (IT) boom of the 1990s and the subsequent bust. Workers in the software and computer services industry were much more likely to have been absent from the Georgia workforce prior to the boom but were no more likely than workers from other industries to have exited the workforce during the bust. Consequently, the Georgia workforce likely experienced a net gain in worker human capital as a result of being an area of concentration of IT-producing activity during the IT boom.
Keywords: 330; Informationstechnik; Konjunktur; Arbeitsmobilität; Georgia (Staat)